Percepción sobre la metodología aprendizaje servicio en la formación académica y social en estudiantes de educación inicial en la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana 2020 - Guevara Rodriguez de Ruiz, Gimena de los Angeles (2021)
The main objective of the research was to describe the perception of initial education students about the service-learning methodology in their academic and social training at the Faculty of Education Sciences and Humanities of the National University of the Peruvian Amazon in 2020. The type of research adopted is the descriptive one whose design has been cross-sectional and field. The study population and sample consisted of 206 initial education students. The instrument used was a questionnaire previously validated by judges, and the data collection technique used was the survey. The main finding of the research has been that initial education students have a perception that the service-learning methodology is quite useful in 77.2% (159 students), less predominance of the unhelpful level (2.9%, 6 students), and somewhat useful in 19.9%, (41 students).